Flavonoids and triterpenes from the leaves of artocarpus fulvicortex - Jamil, Shajarahtunnur; Bakhtiar, M. Taher; M Sirat , hasnah (Natural Product Inc., 2012)
Five flavonoids, 5-hydroxy-(6:7,3:4)-di(2,2- dimethylpyrano)flavone 1, carpachromene 2, cycloartocarpesin 3, norartocarpetin 4 and 2′-hydroxy-4,4′,6′- trimethoxychalcone 5, along with three triterpenes, friedelin 6, lupeol 7 and β-sitosterol 8 were isolated for the first time from the leaves of Artocarpus fulvicortex F.M. Jarrett. The structures of these compounds were established by analysis of their spectroscopic (1D and 2D NMR) and spectrometric (MS) data, as well as by comparison of these with those reported in the literature.